Classification and analysis of land cover changes in Khabat District, using Google earth engine (GEE) during the period 1993-2023 - حسن, م.م.جێگرحسن محمود; خضر, ا.د.طارق خضرحسن (Sulaimani Journal for Humanities, 2025)
Identification and exploration of land cover is a necessity and important indicator to present the levels of environmental change in the research area, considering increase in human activities, environmental situations, and associated hazards, monitoring dynamics of land cover change, and loss of diversity of each of the land cover categories in the area. Thus, in this perspective the research investigates the classification and analysis of land cover changes in Khabat district. The research used random forest classification method in Google Earth Engine (GGE) platform during thirty years from 1993-2023, based on the Random Forest (RF) algorithm, by using of multitemporal satellite imagery from the Landsat. The aim of this research is to use technology tools (RS, GIS, GEE) to monitor, analyse and create land cover classification, and calculate changes in different types of land cover and interpret the causes and inform in the future, include Built up area, cultivated land, forests and shrub land, Grassland, uncultivated land, and water bodies. The results show significant changes in land cover during the research period, each of the area of the categories of Built-up area, cultivated land, forests and shrub land, Grassland, water body have increased, in such a way that the Built-up area during research has been increased by 2.08%. Cultivated land accounted for 5.01%, forests and shrub land increased by 0.39%, Grassland area by 1.02%, and water body by 0.12% increased, reflecting the impact of human activities and the economic situation in the study area. On the contrary, just non-cultivated land cover decreased by 8.60%, showing differences in the directions of each of the land cover categories, this research emphasizes the use of (GEE) as an effective tool for long-term land cover monitoring, and provides critical insight into (temporal – spatial) dynamics. The future research should focus on integrating (socio-economic) data to further explain the engine of land cover change on the one hand and continuously improve land use management approaches and aerial imagery data in land cover change analysis on the other to make effective decisions Management strategies for each of the land cover categories should be given.
Keywords: Classification; Land Cover; (GEE); Khabat District